Serum vitamin levels in multiple system atrophy: A case-control study - Chen, Daji; Wan, Linlin; Chen, Zhao; Yuan, Xinrong; Liu, Mingjie; Tang, Zhichao; Fu, You; Zhu, Sudan; Zhang, Xuewei; Qiu, Rong; Tang, Beisha; Jiang, Hong (Frontiers in Aging Neuroscience, 2023)
There is increasing evidence suggesting that vitamins may play important roles in the pathogenesis of multiple system atrophy (MSA). In this study, we investigated whether serum vitamin levels, including vitamin A, B1, B2, B9 (folate), B12, C, D, and E, were discriminative among MSA patients (N=244), Parkinson’s disease (PD) patients (N=200) and healthy controls (N=244). Compared with the healthy controls, decreased serum vitamin B9 levels and increased serum vitamin A and C levels were detected in MSA patients. No difference was detected between MSA and PD patients. In MSA patients, significant correlation was found between serum vitamin levels and relevant clinical parameters. In addition, ROC analysis showed potential diagnostic value of the combination of vitamin A, B9, and C in distinguishing MSA patients from healthy controls. The significant changes in the blood vitamin spectrums of MSA patients suggested that dysregulation of vitamins homeostasis might play an important role in the pathogenesis of MSA.